Swimming behavior of Daphnia dentifera is influenced by Australozyma monospora infection - Jeannette E. Cullum; Vanessa Rivera-Quiñones; Ilona A. Menel; Zoi Rapti; Carla E. Cáceres (PLoS ONE, 2026)
By changing the behavior of infected hosts, pathogens can shape the outcome of both disease transmission and other interspecific interactions within the food web. This change in behavior is most often recognized in trophically-transmitted parasites, where changing the behavior of an intermediate host can increase the rate at which the parasite is transmitted to the next host. However, behavioral changes also occur in terminal hosts. In a laboratory experiment, we investigated if infection by the ascomycete yeast Australozyma monospora (formerly Metschnikowia bicuspidata ) and/or the time since infection changes the swimming behavior over time of its freshwater cladoceran host, Daphnia dentifera . Infection influenced the net distance and total distance traveled as well as the swimming speed and mean depth of the Daphnia . Uninfected individuals traveled further, both in terms of net distance and total distance, and they also swam faster. The influence of time since infection was more nuanced. Swimming speed, net distance, and total distance traveled varied with time, but mean depth did not. Though we found no main effect of time since infection on mean swimming depth, time did interact with infection status to influence mean depth. A better understanding of how pathogens may alter the movement and habitat selection of infected hosts can help to inform predictive models of disease spread in lakes that are ever-changing due to increased anthropogenic stressors.